The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.17921/1415-6938.2020v24n5-esp.p489-495
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Quality of Certified and Uncertified Honeys from the Brazilian Semi-Arid Region

Abstract: O Brasil se destaca como um dos principais produtores mundiais de mel. A legislação brasileira estabelece parâmetros de qualidade e análises físico-químicas para avaliar e controlar a qualidade do mel comercializado. Essas análises também são importantes para detectar adulterações que podem causar diversos efeitos negativos aos consumidores. O objetivo deste estudo foi avaliar e comparar a qualidade físico-química de amostras de mel certificadas e não-certificadas produzidas em diferentes cidades da região sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The moisture content of the samples analysed varied from 14.8 to 19.2%, that is, within the limits established by the legislation (≤ 20%). Similarly, Tôrres et al (2020) found moisture ranging from 16.8 to 18.0% in certified and uncertified honeys from the Brazilian Semi-Arid Region.…”
Section: Microbiological and Physicochemical Quality Of Honeymentioning
confidence: 84%
“…The moisture content of the samples analysed varied from 14.8 to 19.2%, that is, within the limits established by the legislation (≤ 20%). Similarly, Tôrres et al (2020) found moisture ranging from 16.8 to 18.0% in certified and uncertified honeys from the Brazilian Semi-Arid Region.…”
Section: Microbiological and Physicochemical Quality Of Honeymentioning
confidence: 84%